The labyrinth - Stålenhag, Simon (Image Comics, Inc., 2020)
"The world is covered by ruins and ash. Remnants of an otherworldly phenomenon have ravaged Earth's atmosphere and forced the few survivors deep underground. When Matt, Sigrid and Charlie leave the isolation of their subterranean outpost, their expedition across the wastelands forces them to confront their own dark history and the madness lurking in our ruined world"--